1989
DOI: 10.1016/0014-5793(89)81098-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neutral endopeptidases (EC 3.4.24.11) and of neutral proteinases (EC 3.4.24.4) using a new sensitive two‐stage enzymatic reaction

Abstract: A sensitive two-stage enzymatic reaction for mammalian and bacterial metalloendopeptidases has been developed using the substrate 3-carboxypropanoyl-alanyl-alanyl-leucine-~nitroanilide supplemented with Streptomyces griseus aminopeptidase. Neutral endopeptidase EC 3.4.24.11 from bovine kidney hydrolyzes the substrate (pH 7.5,25"C) with a catalytic efficiency (k,, = 1.2 x 107 s-r, K,,, = 0.15 mM) of the highest ever reported for the enzyme acting on synthetic chromophoric and fluorogenic substrates. Thermolysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This indicates the disruption of FITC‐Casein by thermolysin activity and thus a loss of fluorescence quenching. The positive control containing phosphoramidon, the chemical inhibitor of thermolysin, does not show any fluorescence [51]. In addition, no fluorescence signal was detected with IMPI‐GST in buffered solution or IMPI‐GST in the final formulation, indicating the inhibition of thermolysin by IMPI‐GST.…”
Section: Resultsmentioning
confidence: 95%
“…This indicates the disruption of FITC‐Casein by thermolysin activity and thus a loss of fluorescence quenching. The positive control containing phosphoramidon, the chemical inhibitor of thermolysin, does not show any fluorescence [51]. In addition, no fluorescence signal was detected with IMPI‐GST in buffered solution or IMPI‐GST in the final formulation, indicating the inhibition of thermolysin by IMPI‐GST.…”
Section: Resultsmentioning
confidence: 95%
“…An increase in absorbance at 405 nm was followed for 60 min and ⌬E/min determined from the linear part of the curve. Neprilysin activity was determined as described (22), but with Suc-Ala-Ala-Phe-pNA as substrate (23). To cleave the resulting Phe-pNA 5 l of 0.5 mg/ml membrane alanine AP (Sigma) was included in the test, which had been shown earlier to be well above the expected activity of neprilysin.…”
Section: Methodsmentioning
confidence: 99%
“…We found that endopeptidase activity of spermatozoa is proportional to the number of cells per unit volume and, as such, can serve as a measure of accumulation (unpublished data). An aliquot of 20 Al from each well was transferred into a microtiter plate and assayed for endopeptidase activity as described (11).…”
Section: Methodsmentioning
confidence: 99%